Bailout and conglomeration - Kim, Se-Jik (Journal of Financial Economics, 2004)
This paper develops a model of business groups in emerging markets where banks cannot accurately distinguish between good (high productivity) and bad (low productivity) borrower firms. For stand-alone firms, banks can infer the proportion of bad firms among those that default on contracted debt repayments, and might optimally choose to liquidate all defaulting firms in order to reduce the number of bad firms. Business groups, however, obscure the productivity of individual firms. The optimal policy might then be full bailout so as not to risk eliminating good firms. Given the bank's bailout policy, risk-averse firms might form a conglomerate to reduce the risk of liquidation.